Effects of Bifemelane on the Calcium Level and ATP Release of the Human Origin Astrocyte Clonal Cell - Yoshitoku Yoshida; Haruno Kumagai; Yoshiumi Ohkubo; Remi Tsuchiya; Mitsuhiro Morita; Hiroyoshi Miyakawa; Yoshihisa Kudo (Elsevier, 2006)
The effect of bifemelane hydrochloride (bifemelane) was examined on human origin astrocyte clonal cells (Kings-1). Bifemelane (125 - 1000 µM) induced a dose-dependent increase in the intracellular calcium concentration ([Ca2+]i). In the highest concentration (1000 µM), the drug caused the second large increase in [Ca2+]i during the washing. The increase that occurred during the administration partially remained in the Ca2+-free medium and was blocked by 2-aminoethoxydiphenyl borate (2-APB), an IP3-receptor blocker, indicating that the source of Ca2+for the increase could be ascribed to the intracellular store. The increase in [Ca2+]i was not observed during washing with Ca2+-free medium, but was observed when the washing was performed with Ca2+-containing medium. Bifemelane caused a dose-dependent ATP release, but histamine and carbachol, which induced a large increase in [Ca2+]i, had no effects on the ATP release. The effects on the [Ca2+]i were blocked by pretreatment with pyridoxal phosphate-6-azophenyl-2',4' disulfonic acid, a P2-receptor antagonist. Although the mechanisms of ATP release induced by the drug have not been elucidated yet, the present results demonstrate that the increase in [Ca2+]i induced by bifemelane is not due to its direct effect on the cells, but is dependent upon the ATP released from the cells. Keywords:: human astrocyte, bifemelane, ATP release, store operated Ca2+ entry, intracellular Ca2+ store